Vibrational spectroscopy with neutrons : with applications in chemistry, biology, materials science and catalysis - Mitchell, P. C. H. (Philip Charles Harry) (Series on neutron techniques and applications ;, 2005)
Inelastic neutron scattering (INS) is a spectroscopic technique in which neutrons are used to probe the dynamics of atoms and molecules in solids and liquids. This book is the first, since the late 1960s, to cover the principles and applications of INS as a vibrational-spectroscopic technique. It provides a hands-on account of the use of INS, concentrating on how neutron vibrational spectroscopy can be employed to obtain chemical information on a range of materials that are of interest to chemists, biologists, materials scientists, surface scientists and catalyst researchers. This is an access.